2013 IEEE 3rd Portuguese Meeting in Bioengineering (ENBENG) 2013
DOI: 10.1109/enbeng.2013.6518437
|View full text |Cite
|
Sign up to set email alerts
|

Photoplethysmographic logger with contact force and hydrostatic pressure monitoring

Abstract: Esta cópia da tese é fornecida na condição de que quem a consulta reconhece que os direitos de autor são pertença da Universidade de Coimbra e que nenhuma citação ou informação obtida a partir dela pode ser publicada sem a referência apropriada.This copy of the thesis has been supplied on condition that anyone who consults it is understood to recognize that its copyright rests with University of Coimbra and that no quotation from the thesis and no information derived from it may be published without proper ack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…There is a 4.19% to 4.76% deviation between the content of blood oxygen derived from the two curves, and the impact of the pressure can induce a variation of 0.35% to 6.2%. The presented data matches findings from previous research [44] (in small loads, Santos' study demonstrated a 7% variation, utilizing wavelengths of 660 nm and 905 nm; Similarly, Dresher's research yielded a result of 5.1%). When setting up the empirical calibration curve for oximetry, it is imperative to consider the impact of this pressure-induced variation.…”
Section: Oxygen Saturation Analysissupporting
confidence: 89%
“…There is a 4.19% to 4.76% deviation between the content of blood oxygen derived from the two curves, and the impact of the pressure can induce a variation of 0.35% to 6.2%. The presented data matches findings from previous research [44] (in small loads, Santos' study demonstrated a 7% variation, utilizing wavelengths of 660 nm and 905 nm; Similarly, Dresher's research yielded a result of 5.1%). When setting up the empirical calibration curve for oximetry, it is imperative to consider the impact of this pressure-induced variation.…”
Section: Oxygen Saturation Analysissupporting
confidence: 89%
“…This band would apply a skin pressure of about 75 mmHg and, due to its compliance, it would hold steady the applied pressure while the finger was in different positions. Another force measuring modality to integrate with a PPG sensor is a Force Sensing Resistor (FSR, Interlink Electronics, Camarillo, CA, USA), as done by Santos et al [ 214 ]. Liu et al implemented a fiber Bragg gating to measure applied pressure [ 215 ].…”
Section: External Factorsmentioning
confidence: 99%
“…The PPG was recorded with a custom made probe and front end circuit [29] that contains a red and infrared LED but only the red channel was used. The electrical signal was then digitized with a National Instruments data acquisition device (NI-DAQ 6210) connect to the host PC.…”
Section: In Vivo Testmentioning
confidence: 99%